CLOZAPINE ON PARANOID SCHIZOPHRENIA WITH OBESITY: A CASE REPORT - Krisna Arijaya, Dewa Nyoman (E-Jurnal Medika Udayana, 2015)
Treatments   of   schizophrenia   using   atypical   antipsychotics   provide   remission   of symptoms and side effects differ between individuals. The use of the method by finding the right medication often has an impact on patient adherence to treatment. In the case of  a  female  patient  aged  26  years  was  diagnosed  with  paranoid  schizophrenia  and clozapine  treatment  using  2x25  mg  for  6  months.  Schizophrenic   symptoms  had subsided  and  the  patient  can  work,  but  the  treatment  was  stopped  by  the  parents. Treatment was discontinued because of patient body weight increased to 80 kg from initial weight 65 kg. Clozapine increases the weight by several mechanisms.  Genetic and environmental influences susceptibility to gain weight. Weight gain can also cause a large enough increase in obesity-related comorbidities and health risks such as type II diabetes mellitus, hypertension, hear t  disease and cancer.  Subsequent  treatment  be changed  using  atypical  antipsychotics  risperidone  at  a  dose  equivalent.  Given also educate and maintain compliance with treatment.
Keywords: clozapine, paranoid schizophrenia, obesity